Excel for engineers and scientists - Bloch, S. C. (John Wiley and Sons, 2000)
Getting started. Surfing the spreadsheet. Graphing basics. Quick-start math. Differentiation and integration. Engineering functions. Complex math. Differential equations. Analysis toolpak. Excel in the lab.